1 and 2 Timothy/Titus - Liefeld, Walter L. (Grand Rapids, MI Zondervan, 1999)
Includes bibliographical references and indexes.
Brethren writer.
Keywords: Bible. N.T. Timothy -- commentaries; Bible. N.T. Titus -- commentaries